Photodynamic Modulation of Type 1 Interferon Pathway on Melanoma Cells Promotes Dendritic Cell Activation - Lamberti, María Julia; Mentucci, Fátima María; Roselli, Emiliano; Araya, Paula; Rivarola, Viviana Alicia; Rumie Vittar, Natalia Belén; Maccioni, Mariana (Frontiers in Immunology, 2019)
The immune response against cancer generated by type-I-interferons (IFN-1) has recently described. Exogenous and endogenous IFN-/β have an important role in immune surveillance and control of tumor development. In addition, IFN-1s have recently emerged as novel DAMP for the consecutive events connecting innate and adaptive immunity and they also have been postulated as an essential requirement for induction of immunogenic cell death (ICD). In this context, Photodynamic therapy (PDT) has been previously linked to the ICD. PDT consists in the administration of a photosensitizer (PS) and its activation by irradiation of the affected area with visible light producing excitation of the PS. This leads to the local generation of harmful reactive oxygen species (ROS) with limited or none systemic defects. In the current work, Me-ALA inducing PpIX (endogenous PS) was administrated to B16-OVA melanoma cells. PpIX preferentially localized in the endoplasmic reticulum (ER). Subsequent PpIX activation with visible light significantly induced oxidative ER-stress mediated-apoptotic cell death. Under these conditions, the present study was the first to report the in vitro upregulation of IFN-1 expression in response to photodynamic treatment in melanoma. This IFN- transcripts upregulation was concurrently with IRF-3 phosphorylation, at levels that efficiently activated STAT1 and increased ligand receptor (cGAS) and ISGs (CXCL10, MX1, ISG15) expression. The IFN-1 pathway has been identified as a critical molecular pathway for the antitumor host immune response, more specifically for the dendritic cells (DCs) functions. In this sense, PDT-treated melanoma cells induced IFN-1-dependent phenotypic maturation of monocyte-derived dendritic cells (DCs) by enhancing co-stimulatory signals (CD80, MHC-II) and tumor-directed chemotaxis. Collectively, our findings showed a new effect of PDT-treated cancer cells by modulating IFN-1 pathway and its impact on the activation of DCs, emphasizing the potential relevance of PDT in adoptive immunotherapy protocols.